A flexible calibration method connecting the joint space and the working space of industrial robots. Issue 3 (21st May 2018) - Cai, Ying; Yuan, Peijiang; Chen, Dongdong
Abstract : Purpose: To improve the accuracy of the industrial robots' absolute positioning, a Kriging calibration is proposed. Design/methodology/approach: This method particularly designs a semivariogram for connecting the joint space and the working space. After that, Kriging equations are determined and solved to predict the position errors of targets. Subsequently, a simple and convenient error compensation, which can be implemented on the control command, is proposed. Findings: The verification experiment of the position-error multiplicity and the Kriging calibration experiment are done in the KUKA R210 R2700 industrial robot. The position-error multiplicity experiment reveals that the position error of the industrial robot varies with the joint angle sets. Besides, the Kriging calibration experiment shows that the maximum of the spatial position errors is reduced from 1.2906 to 0.2484 mm, which reveals the validity of the Kriging calibration. Originality/value: The special designed semivariation allows this method to be flexible and practical. It can be used in various fields where the angle solutions of industrial robots should be adapted according to the optimal demand and the environment, such as the optimal trajectory planning and the obstacle avoidance. Besides, this method can provide accuracy positioning results.